Η επίδραση της μουσικοθεραπείας ως ανακουφιστική φροντίδα σε ασθενείς τελικού σταδίου και σε ασθενείς με χρόνιες ασθένειες - Κέρμανου, Γρηγορία (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: The use of music therapy in palliative care is a cotemporary tool in the effort to improve the quality of life of people with chronic diseases or people who are terminally ill. However, the application of music therapy in hospitals is not very common, but rather its use is limited. Goal: The goal of the present study was to investigate the field of music therapy in literature as a mean to relief terminally ill patients and patients with chronic diseases. The particular goals of this study, was to point out the effectiveness of music therapy in relation to pain, stress, cancer and others chronic diseases. Design and Method: The method used, was the search of the relevant Greek and English bibliography in databases (such as MEDLINE, PUBMED, SCIENCE DIRECT, EBSCO). In this paper, it was used studies, books and scientific articles which they had as subject the use of music therapy in palliative care in terminally ill patients and patients with chronic diseases. Results: Most of the studies refer to music therapy as a positive factor in patients with chronic diseases and patients who are terminally ill. Despite of that fact, in the analysis of the experimental data it seems that there is no statistical difference which will prove that music therapy is a basic dimension of the palliative care. Discussion: In spite of the idea that many studies present and promote a positive image towards the use of music therapy in palliative practice, there is no general approval of the music therapy as a complementary therapy. As a result, it is needed more research and investigation so that to be proven the effectiveness or not of music therapy in palliative care in patients with chronic or terminal illnesses.
Keywords: Music therapy; Palliative Care; Cancer--Nursing; Heart--Diseases--Patients; Pain, Intractable--therapy; Cancer--Palliative treatment